ARTICLE SOCIAL CAPITAL-BASED COFFEE FARMERS' CAPACITY DEVELOPMENT - Selvita Andriani (Yayasan Amanah Nur Aman, 2026)
Semende Darat Ulu (SDU) District is a major center for robusta coffee production in Muara Enim Regency, South Sumatra. However, this potential has not been fully utilized due to low post-harvest quality, price fluctuations, and the dominance of middlemen in the trade chain. This conceptual research aims to design a social capital-based coffee farmer capacity development model as a more sustainable alternative approach compared to conventional technical programs. Using a sociological approach, this research identifies and capitalizes on Semende's social networks, trust relationships, collective norms, and local customary values, including the Tunggu Tubang system, as the foundation for strengthening farmer capacity. The developed intervention model combines mentoring and participatory training to encourage collective behavioral change. The research results in a draft integrated implementation model titled